Effect of Omega-3 Fatty Acid in Dry Eye Syndrome - Shrestha Joshi, Leesha; Kaiti, Raju; Shyangbo, Ranjila; Bogati, Birkha; Nepal, Sabina; Dahal, Grishma (Nepalese Journal of Ophthalmology, 2025)
Introduction: Dry eye syndrome (DES) is a multifactorial disease of the ocular surface. It is accompanied by increased osmolarity of tear film and inflammation of the ocular surface. Objective: To evaluate the impact of Omega-3 fatty acids in patients with DES and compare their effectiveness with topical lubricating agents in relieving subjective symptoms and improving clinical signs. Methodology: A prospective interventional study involving patients diagnosed as ‘moderate’ to ‘severe’ Dry Eye Syndrome were included by convenience sampling. The inclusion criteria were patients above 20 years who were diagnosed as dry eye in the Outpatient Department in Nepal Eye Hospital. All the samples underwent detailed comprehensive eye examination, followed by a detailed dry eye evaluation. The severity of the dry eye was assessed both objectively based on ‘Schirmer’s-II test’ and ‘Tear Film Break Up Time (TBUT)’, and subjectively by Ocular Surface Disease Index (OSDI) questionnaire. Each patient was prescribed Omega-3 fatty acid for three months and were followed up after one month and three months. Result: The baseline Schirmers-II, TBUT and OSDI Score was 5.85 + 5.38 mm, 4.00 + 2.077 seconds, and 38.61 + 8.35 respectively. No significant change in the Schirmer’s score was noted after the end of treatment period, but the TBUT and OSDI Score improved significantly. Conclusion: This study shows that omega-3 fatty acid has significant role in improving TBUT and subjective symptoms in patients with dry eye syndrome but has no effect on the Schirmer’s test.